2016
DOI: 10.20452/pamw.3501
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of small intestinal bacterial overgrowth (SIBO) in adult patients with type 1 diabetes and relationship with metabolic control and the presence of chronic complications of the disease

Abstract: INTRODUCTION Gastrointestinal symptoms may occur in 50% to 70% of patients with diabetes. OBJECTIVES The aim of this study was to evaluate the prevalence of small intestinal bacterial overgrowth (SIBO) in patients with diabetes, as well as the relationship between SIBO and metabolic control of diabetes and the presence of chronic complications of the disease. PATIENTS AND METHODSThe study group included 148 patients with type 1 diabetes, treated in the years 2013-2015. The control group consisted of 41 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 6 publications
0
20
4
Order By: Relevance
“…In a study by Faria et al, 2013, the prevalence of SIBO was 11.5% which is lower compared to the prevalence of SIBO observed in the present study (22.7% in T1DM patients and 37.5% in T1DM ≥5 years disease duration). In contrast to findings in the present study, recently another study observed lower (37.8%) prevalence of SIBO in adult patients with type 1 diabetes in comparison with controls (73%) although the % of SIBO in patients and controls in their study was higher than observed in the present study. However, the association between hyperglycaemia, oxidative stress, inflammatory cytokines, OCTT, and SIBO in same patients of T1DM has never been studied.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study by Faria et al, 2013, the prevalence of SIBO was 11.5% which is lower compared to the prevalence of SIBO observed in the present study (22.7% in T1DM patients and 37.5% in T1DM ≥5 years disease duration). In contrast to findings in the present study, recently another study observed lower (37.8%) prevalence of SIBO in adult patients with type 1 diabetes in comparison with controls (73%) although the % of SIBO in patients and controls in their study was higher than observed in the present study. However, the association between hyperglycaemia, oxidative stress, inflammatory cytokines, OCTT, and SIBO in same patients of T1DM has never been studied.…”
Section: Discussioncontrasting
confidence: 99%
“…Another peculiarity of chronic gastritis in patients with T2DM is commonly diagnosed SIBO (75% vs 41.3% non-diabetic cases). In contrast, some literature data suggest that patients with T1DM are diagnosed with SIBO in 37.8% cases [30]. Such symptoms as bloating, belching and nausea in patients with chronic gastritis and T2DM are significantly associated as with HP infection, as with SIBO, which has been diagnosed in 77.5% HP-positive cases and 66.7% HP-negative cases.…”
Section: Discussionmentioning
confidence: 94%
“…The studies were subgrouped based on the SIBO diagnostic test used. The pooled prevalence of SIBO was 31% (95% CI 18-43%) in six studies [13,14,18,22,24,28] using the LBT and 29% (95% CI 14-43%) in seven studies [12, 19-21, 23, 25, 26] using the GBT. Two studies [27,28] using JACs showed a prevalence of 39% (95% CI 12-66%) (Fig.…”
Section: Prevalence Of Sibo In Diabetic Patientsmentioning
confidence: 99%
“…Studies on the relationship between DM and risk of SIBO have yielded inconsistent results. Notably, diabetes patients have been reported to exhibit increased risks of SIBO [12] , but several studies have reported inconsistent results [13][14] . Therefore, we conducted a systematic review and meta-analysis to investigate the relationship between DM and the risk of SIBO by summarizing all of the available data.…”
Section: Introductionmentioning
confidence: 99%